2019
DOI: 10.2135/cropsci2019.02.0126
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Phenotypic Traits in Annual Ryegrass

Abstract: Characterizing phenotypes in germplasm collections and making data publicly available is crucial to ensure the utilization of the accessions in breeding programs. Variance component estimates are used to calculate genetic parameters needed to make strategic decisions for germplasm conservation and its utilization in plant breeding. This information is lacking for annual ryegrass (Lolium multiflorum Lamarck) germplasm from the USDA National Plant Germplasm System (NPGS). In this study, we estimated variance com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In common bean ( Phaseolus vulgaris L.), the temporal control of flowering initiation determined the time invested in vegetative growth and, consequently, the vegetative resources available during reproduction (González et al., 2016). A negative correlation between two traits suggests that an increase in time or in number of one trait has an adverse effect on the other trait (Rios et al., 2019). The high negative correlation found in our study between DFPM and DTF indicates that the longer the plant takes to set flowers, the shorter the period for pod formation and/or maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In common bean ( Phaseolus vulgaris L.), the temporal control of flowering initiation determined the time invested in vegetative growth and, consequently, the vegetative resources available during reproduction (González et al., 2016). A negative correlation between two traits suggests that an increase in time or in number of one trait has an adverse effect on the other trait (Rios et al., 2019). The high negative correlation found in our study between DFPM and DTF indicates that the longer the plant takes to set flowers, the shorter the period for pod formation and/or maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The reproduction index ranged from .51 to .52 for M. enterolobii and between .86 and .92 for M. incognita (Dareus et al., 2021). Combining multiple traits into one cultivar is a challenge for breeders, especially for traits with negative correlations, and indirect selection using various positively correlated traits may reduce phenotyping efforts (Rios et al., 2019). Moderate correlations between days to flowering and dry biomass yield ( r g = .54) and plant height ( r g = .51) were reported in cowpea (Gerrano et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Red clover, particularly in Europe, and annual ryegrass are species with commercial success of tetraploid cultivars. Rios et al, 2015, 2019) recently reported ploidy characterization of 139 annual ryegrass accessions obtained from the USDA Germplasm Resources Information Network (GRIN) germplasm collection of annual ryegrass plus 15 Florida experimental lines and 13 commercial cultivars. Only 16% (27 out of 167) of accessions evaluated were tetraploid, all developed through doubling chromosome numbers since tetraploid annual ryegrass is not known to exist in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…In the last century, autopolyploidy has been viewed as a breakthrough tool for yield enhancement, but research soon demonstrated otherwise in most major food crops.Commercial success of polyploidy in cultivar development has primarily been limited to some floriculture crops and to certain forage species. Red clover, particularly in Europe, and annual ryegrass are species with commercial success of tetraploid cultivars Rios et al, 2015Rios et al, , 2019. recently reported ploidy characterization of 139 annual ryegrass accessions obtained from the USDA Germplasm Resources Information Network (GRIN) germplasm collection of annual ryegrass plus 15 Florida experimental lines and 13 commercial cultivars.…”
mentioning
confidence: 99%
“…Tetraploid accessions, for example, have significantly larger seeds compared to diploid seeds (Sugiyama, 1998). In addition to these, ploidy determines morphological changes in the plant, which must be considered for the indication of the sowing rate to be used (Rios et al, 2019).…”
Section: Introductionmentioning
confidence: 99%